HE ANALYSIS OF JUDGE’S DECISION ON MAFQUD’S HUSBAND IN CASE OF CLAIM FOR DIVORCE IN PONOROGO RELIGION COURT AND THE LAW IMPACT OF THE MAFQUD HUSBAND (Analysis of Decision Number. 959/Pdt. G/2018/PA. PO) - Ria Rahmawati; Ihsan Nur Hakim (Universitas Darussalam Gontor, 2019)
This research is a study on divorce claims in the Ponorogo Religious Court with case number 959 / Pdt. G / 2018 / PA.PO that involves one of the parties that is not known to involvehim (Husband / Defendant Ghoib). On the verdict, the Judgegranted the Plaintiff’s claim and dropped the Defendant’s ba’inshugra to the plaintiff (wife) and the defendant (husband) hasnot lived together for 7 years, because the husband disappearedand was not recognized as completing it. This study elaborates thediscussion of the Panel of Judges of the Religious Courts regardingthe divorce case Number 959 / Pdt. G / 2018 / PA. PO aboutmafqud husband (ghoib) in a divorce case, then think about howit happened to the Plaintiff (wife) due to mafqud’s husband. Fromthe results of this study, it is known that the decision of the Judges of the Ponorogo Religious Court in the case of divorce Number 959 / Pdt. G / 2018 / PA. The PO that was canceled by divorceone ba’in shugra through verstek, for reasons of more than 7 yearsadded was also not approved until now, and this became the wife’sreason to not be able to maintain his marriage. Subsequently, thefinding out some analysis obtained from the case number 959 /Pdt. G / 2018 / PA. PO. So that the judge can determine thereason for the divorce stated in Article 19 letter “b” Government Regulation Number 9 of 1975. Article 116 letter “b” Compilation f Islamic Law as “one of the parties” leaves the other party for 2(two) years together without permission from the other party andwithout a valid reason or other matters beyond its ability. Decisionissued then it does not occur in the future if there is a party thatis harmed and appealed for the decision.